Pengaruh Pupuk Hayati dan Pupuk Anorganik Terhadap Beberapa Sifat Kimia Tanah Serta Hasil Tanaman Bayam Cabut (Amaranthus tricolor) di Tanah Inceptisol Desa Pedungan - PRIAMBODO, SEINA RIZKY; SUSILA, KETUT DHARMA; SONIARI, NI NENGAH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.8, No.1, Januari 2019, 2019)
The Effect of Biofertilizers and Anorganic Fertilizers to Several Soil Chemical Properties and Spinach (Amaranthus tricolor) in Pedungan Village Inceptisol The aim of this study is to know the effect of interaction between biofertilizers and inorganic fertilizers on soil chemical properties and yield of spinach in Pedungan Inceptisol. This research was conducted from October 2017 to February 2018 at the greenhouse. The experiment located in Pedungan Village and the Soil and Environmental Laboratory, Agriculture Faculty of Udayana University. Randomized Block Design (RBD) with 9 treatments and 3 replications were used in this experiment. The data were analyzed by using the Costat program and continued by the LSD test at 5% level if the treatment was significantly different. The variables observed in this study consisted of soil chemical properties and production of plants. The result of this experiment showed that there are no interaction between biofretilizer and inorganic fertilizer on all of parameters observed. The effect of biofertilizers had a significant diferences on all of parameters, while in using inorganic fertilizers only on the half parameters. The treatment of biofertilizers at a dose of 20 mL had a significant effect on the improvement on all parameters, while inorganic fertilizer treatment at half of the recommended dose had the same effect as the treatment of real recomended dose for increasing the total N, K, soil pH, and plant height.